A glycopyrronium bromide 1% cream for topical treatment of primary axillary hyperhidrosis: efficacy and safety results from a phase IIIa randomized controlled trial. (2nd March 2021) - Abels, C.; Soeberdt, M.; Kilic, A.; Reich, H.; Knie, U.; Jourdan, C.; Schramm, K.; Heimstaedt‐Muskett, S.; Masur, C.; Szeimies, R.‐M.
Summary: Background: Effective topical treatment options for patients with primary axillary hyperhidrosis (PAHH) are limited. A phase I trial showed promising results regarding the efficacy and safety of a topical cream containing glycopyrronium bromide (GPB). Objectives: To assess the efficacy, safety and tolerability of a 4‐week topical treatment of GPB 1% cream in patients with PAHH vs. placebo. Methods: In total, 171 patients (84 receiving placebo; 87 receiving GPB 1%) with PAHH were included in the 4‐week, multicentre, randomized, double‐blind, placebo‐controlled phase IIIa part of the pivotal study. Sweat production was measured by gravimetry. Patients rated the impact of disease with the Hyperhidrosis Disease Severity Scale (HDSS) and Hyperhidrosis Quality of Life Index (HidroQoL © ). Results: Absolute change in sweat production from baseline to day 29 in logarithmic values was significantly larger in the GPB 1% group compared with the placebo group ( P = 0·004). The improvement in HidroQoL exceeded the minimal clinically important difference of 4. The proportion of responders was twofold higher for sweat reduction (–197·08 mg GPB 1% vs. –83·49 mg placebo), HDSS (23% GPB 1% vs. 12% placebo) and HidroQoL (60% GPB 1% vs. 26% placebo). Treatment was safe: most treatment‐emergent adverse effects were mild or moderate, and transient. Local tolerability was very good, with 9% of patients having only mild or moderate application‐site reactions. The most reported adverse drug reaction was dry mouth (16%), an expected anticholinergic effect of the treatment. Conclusions: GPB 1% cream may provide an effective new treatment option exhibiting a good safety profile for patients with PAHH. The long‐term open‐label part (phase IIIb) is ongoing. Abstract : What is already known about this topic? Hyperhidrosis (HH) places a great burden on patients. Topical application of anticholinergic substances may provide an effective treatment for focal HH with an improved safety profile vs. oral application. A phase I dose‐finding study on the topical application of a formulation containing glycopyrronium bromide (GPB) showed that a 1% cream could be an effective new treatment option with a good safety profile for patients with primary axillary HH (PAHH). What does this study add? In this part of the pivotal phase III trial, compared with those given placebo, patients with PAHH using a GPB 1% cream achieved a significant reduction in sweat production and improved quality of life. GPB 1% had a good safety profile and excellent tolerability at the application site. Topical GPB is effective for PAHH and that a cream formulation is beneficial in terms of local tolerability and systemic safety. Plain language summary available online